Mission Note Bangladesh, March 15-31, 2009 - World Bank (Washington, DC, 2013)
The Government of Bangladesh has requested the World Bank to provide further assistance to the livestock and dairy sectors. During a mission of the Sector Manager of Agriculture and Rural Development (ARD) of the South Asia region of the World Bank to Bangladesh in November 2008, the Secretary of the Ministry of Livestock and Fisheries (MOFL) of the former Caretaker Government of Bangladesh (BD) requested the Sector Manager for assistance to the development of the dairy and fisheries subsectors to support the livelihoods of the rural people and contribute to the economic growth of the country. The secretary of the MOFL also reminded the Bank of its proposal for an investment request for dairy development to the Bank sent in 2007. In response, the Bank agreed to carry out a technical mission to review the current state of the livestock sector (with special focus on the dairy sub-sector) and the fisheries sector, particularly inland fishery production (including freshwater capture and freshwater aquaculture). The mission reviewed policy, technical and administrative aspects in order to identify key bottlenecks and assess the scope for Bank-supported further development of the sectors. This request of the Government is consistent with the emphasis in the Poverty Reduction Strategy Plan (PRSP) on further development of the livestock and fisheries sectors which together account for 7 percent of total Gross Domestic Product, or GDP (3 percent livestock, 4 percent fisheries) and 33 percent of agricultural GDP).